Improving Compliance towards International Humanitarian Law: Filling in the Gaps? - Hamidah, Fitry Nabiilah; Muhammadin, Fajri Matahati (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2024)
International humanitarian law (IHL) aims to regulate the conduct of parties during hostilities to mitigate the horrors of war, providing safeguards for civilians through instruments such as the 1949 Geneva Conventions, 1977 Additional Protocols, customary international humanitarian law, and principles of IHL. Despite its comprehensive framework, applicable to both States and non-state armed groups, non-compliance remains a significant challenge, undermining its credibility and effectiveness. This paper analyzes the current compliance mechanisms, identifies gaps and factors influencing compliance, examines the impacts of these gaps, and proposes strategies to enhance the effective implementation and adherence to IHL in both international and non-international armed conflicts. To address gaps in IHL compliance mechanisms, this paper recommends that States establish permanent platforms for regular IHL discussions and provide institutional support to existing mechanisms. It also emphasizes that considering a multidisciplinary approach towards factors influencing compliance, the enhancement of the roles of national red cross and red crescent societies in the dissemination of IHL and non-governmental organizations and international organizations in humanitarian engagement with all parties to the conflict, as well as fostering cultural sensitivity through open and constructive engagements are essential to develop a holistic IHL compliance system.